PENGARUH ETIKA BISNIS ISLAM, KUALITAS PELAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN AUSATH MART 1 PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Ika Susanti, Nawal; Eka Nurdiana, Melani (Jurnal Ekonomi Syariah Darussalam, 2023)
The purpose of this study was to determine the effect of Islamic business ethics (X1), service quality (X2) and product quality (X3) on consumer satisfaction at Ausath Mart 1 Pondok Pesantren Darussalam Blokagung Banyuwangi (Y) partially and simultaneously. The type of research in this research is quantitative research with associative method. The sampling technique used Probability Sampling with simple random sampling technique. In taking the sample, the researcher used the Slovin formula and obtained a sample of 130 respondents from a population of 200 consumers. The results of the study positively and significantly Islamic business ethics (X1), service quality (X2), and product quality on consumer satisfaction Ausath Mart 1 Pondok Pesantren Darussalam Blokagung Banyuwangi (Y) partially and simultaneously. The conclusion from the results of the linear regression analysis of the coefficient of determination (R2) shows the value of the coefficient of determination is 0.378. This shows that all independent variables, namely Islamic business ethics (X1), service quality (X2), and product quality (X3) have a joint contribution of 37.8% to the consumer satisfaction variable (Y), while the remaining 62 ,2% influenced by other variables not examined.